2018
DOI: 10.1016/j.jasrep.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Integration of neutron-based elemental analysis and imaging methods and applications to cultural heritage research

Abstract: The present paper describes the merits of the combined neutron-based elemental analysis and neutron imaging techniques, called prompt-gamma activation imagingneutron tomography (PGAI-NT), and illustrates its application to cultural heritage science with relevant case studies. The approach is proven to be best applicable to samples with corroded/layered/gilded/painted/coated structures where the surface weighted response would bias the analysis results obtained with simpler, more widespread, but less representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…2007.2-E of the Museum of Fine Arts, Budapest), is used here as a demonstration. Detailed element analysis results [12] and imaging studies [13], as well as the discussion of its cultural-heritage background, have been reported in earlier publications. As illustrated in Fig.…”
Section: Plastic Replica Of An Artifact From 3d Segmented Data For Samentioning
confidence: 99%
“…2007.2-E of the Museum of Fine Arts, Budapest), is used here as a demonstration. Detailed element analysis results [12] and imaging studies [13], as well as the discussion of its cultural-heritage background, have been reported in earlier publications. As illustrated in Fig.…”
Section: Plastic Replica Of An Artifact From 3d Segmented Data For Samentioning
confidence: 99%
“…From the XRF measurements, one can conclude that the objects do not share the same composition, even the ones which were found in the the same archaeological context. For a better characterization of the objects, a more comprehensive analysis procedure is necessary, involving bulk PGAA and neutron imaging [119], [172]. Being the only pear-shaped object from an authentic excavation, a balance weight from Ócsa (catalog number: 92.57.2.B) (seeFigure 41 d) was selected from the Turkish collection for the first preliminary PGAI and neutron imaging tests.…”
Section: Ottoman Weightsmentioning
confidence: 99%
“…Using PGAA, besides the possible alloy components, minor amount of As and Ni could be determined, and in total 7 m% of S, Si, Cl, H and B. These latter elements were found in elevated quantitites at the surface, attributed to soil contamination, or corrosion [172]. In case of bronze objects buried for a long time, the commonly formed minerals on the copper-alloy surface are hydroxy salts with sulphate or chlorine content [177] consistent with the above-mentioned elements.…”
Section: Rivet Of a Dagger From The Bronze Agementioning
confidence: 99%
“…Advanced composition and structure analysis techniques available at large-scale facilities, such as synchrotrons and neutron centres, are capable of characterizing such valuable artifacts nondestructively [1][2][3][4] . While optical photons and X-rays can penetrate a few (hundred) µm into metals 5 , neutrons and gamma rays have an information depth up to a few mm-cm 6 , so they offer either bulk representativity in case of homogeneous samples 7 or local concentrations relevant to an internal gauge volume for nonhomogeneous objects 8 , even if this volume element is inaccessible from outside 9,10,11,12 .…”
Section: Introductionmentioning
confidence: 99%